(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. To avoid temporary hemodialysis, urgent initiated PD (UIPD) has been designed. In these patients, PD is initiated within 3 days after PD catheter placement. In this study, we evaluated the outcomes of UIPD in end-stage renal disease patients compared with the conventional start of PD. Methods. This is a single-center observational study, comparing outcomes of UIPD to conventional initiation of PD. All patients diagnosed with ESRD from March 2013 to February 2019 and were willing for CAPD were recruited. In UIPD group treatment was initiated at day 2 of catheter insertion with a dialysate volume of 1000 mL per dwell for 2 hours gradually increased to 2000 mL per dwell volume by 8 to 10 days. Results. During the study period, 98 patients were started on peritoneal dialysis in our hospital: 35 UIPD, 63 conventional PD. The mean age was 60.81 ± 13.04 years. 67% of patients were males with diabetes mellitus (32%) being the most common cause of CKD. Among the patients in UIPD, the mean age was 58.49 ± 16.1 years, while as in conventional group mean age was 62.10 ± 10.9 years. The Median follow-up time was 381 days. Technique survival was seen in 95 patients (96.9%). There was no difference in technique failure between UIPD vs conventional group. Total complications in our study occurred in 16 patients out of 98 patients during this period. There was no significant difference in the complication rates between the UIPD group and the conventional group. Conclusion. Our study showed that catheter patency, technique survival, and catheter-related complications were comparable between UIPD and conventional start peritoneal dialysis.